CLASSROOM ACTION RESEARCH TO IMPROVE STUDENTS' NUMERACY SKILLS ON INTEGER USING MANIK-MANIK MEDIA - Ndapa Deda, Yohanis; Hijriani, Lailin; Trifosa Alnabe, Ayu (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
This study aims to improve students' numeracy literacy skills on integer operation material using Manik-Manik media. The method used is Classroom Action Research (CAR). Research is carried out in two cycles, and each process consists of three meetings, with stages: planning/preparation of actions, implementation of activities, observation, and reflection. Data collection techniques using observation techniques (teachers and students), learning outcomes tests, and documentation. Based on the results of the research on 25 students, it is known that there was increasing in student learning outcomes from before the action, Cycle I and Cycle II. This is evidenced by the post-test value that was carried out in cycle I, which showed an average value of 59.4, and then the increase in cycle II with an average value of 90.8. The data analysis techniques used are data analysis of observations of teachers and students and analysis of test result data in the form of classical completeness. Based on the research on integer operation material, it was concluded that learning by using Manik-Manik can improve students' mathematics learning outcomes. Thus, using Manik-Manik media can improve students' numeracy literacy skills on integer operation materials. Keywords: Integer, Manik-Manik Media, Numeration Literacy, CAR.